FTSJ2, a heat shock-inducible mitochondrial protein, suppresses cell invasion and migration. - Cheng-Wei Lai; Hsiao-Ling Chen; Ken-Yo Lin; Fang-Chueh Liu; Kowit-Yu Chong; Winston T K Cheng; Chuan-Mu Chen (PLoS ONE)
Ribosomal RNA large subunit methyltransferase J (RrmJ), an Escherichia coli heat shock protein, is responsible for 2'-O-ribose methylation in 23S rRNA. In mammals, three close homologs of RrmJ have been identified and have been designated as FTSJ1, FTSJ2 and FTSJ3; however, little is known about these genes. In this study, we characterized the mammalian FTSJ2, which was the most related protein to RrmJ in a phylogenetic analysis that had similar amino acid sequence features and tertiary protein structures of RrmJ. FTSJ2 was first identified in this study as a nucleus encoded mitochondrial protein that preserves the heat shock protein character in mammals in which the mRNA expressions was increased in porcine lung tissues and A549 cells after heat shock treatment. In addition, a recent study in non-small cell lung cancer (NSCLC) suggested that the FTSJ2 gene is located in a novel oncogenic locus. However, our results demonstrate that the expression of FTSJ2 mRNA was decreased in the more invasive subline (CL1-5) of the lung adenocarcinoma cells (CL1) compared with the less invasive subline (CL1-0), and overexpression of FTSJ2 resulted in the inhibition of cell invasion and migration in the rhabdomyosarcoma cell (TE671). In conclusion, our findings indicate that mammalian FTSJ2 is a mitochondrial ortholog of E. coli RrmJ and conserves the heat shock protein properties. Moreover, FTSJ2 possesses suppressive effects on the invasion and migration of cancer cells.